PERSEKUTUAN PERDATA NOTARIS BERDASARKAN UNDANG-UNDANG JABATAN NOTARIS - Fonni Fonni; Winner Sitorus; Hasbir Paserangi (Faculty of Law, Universitas Riau, 2018)
The Law of Notary Position provides an opportunity for notaries to establish a Civil Partnership of notaries in the performance of their position. This is contrary to the notary profession, since the purpose of the formation of Civil Partnership is to seek the benefit to be distributed to allies as stipulated in the Civil Code. This study aimed to find out and comprehend (1) the formation of a civil partnership of notary in the implementation of the notary’s position: (2) the application of the principles of civil partnership stipulation in the Civil Code to civil partnership of notary. This research is a normative research that is a process to find out laws, legal principles, and legal doctrine to answer the legal problem. This study employed a statutory, comparison, and conceptual approaches.Keywords : Civil Partnership, Notary, Joint Office, Maatschap